Critical Point Equation on 3-Dimensional Trans-Sasakian Manifolds: Dibakar Dey - Team, Support (Thai Journal of Mathematics, 2021)
The object of the present paper is to characterize 3-dimensional trans-Sasakian manifolds satisfying the critical point equation under the condition φ gradα = gradβ. Also, we present few examples which verifies our results.